JAGAT HEROIK PEREMPUAN - Ayub Wahyudin (MUWAZAH : jurnal kajian gender, 2009)
Women in the tradition of the heroic world of the archipelago has entered a “decisive” and “threatening” presence of people for some people. As a result of rebel attacks around the world pierced by gender, women should have a prominent place. But there are efforts to theological, sociological, and culture that strives to create a new birth of compliance “” and “spiritual obedience” to the world of gender, with women as abdun needs (subject). Compliance is sometimes a real tangible in silence as a zombie “-a woman who in her” by the attacks that are considered absolute doctrine. Not a few of them accept injustice, alienation, and even violence that never imagined before. It should be emphasized, that heroic woman in the world there are a number of ideas that always lead to wrong interpretation and the process of exclusion (exemption) for women.